(untitled) (Jurnal Kemanusiaan, 2017)
The present study aimed to investigate student self-rating towards body dissatisfaction, drive for muscularity and self-esteem, as well as to investigate their relationship. Results from a sample of 293 male students from University Malaysia Sabah showed a significant positive relationship between body dissatisfaction and drive for muscularity (r = .22, p < .01). An interesting result was that body dissatisfaction is positively correlated with higher self-esteem (r = .142, p <.05), which was assumed that body dissatisfaction alone was a poor predictor of self-esteem. Culture has its role affecting the values people place on different aspects of the body. By using One-way ANOVA, study found the significant ethnic difference in body dissatisfaction (F(3, 289) = 3.779, p < .05) and drive for muscularity (F(3, 289) = 5.116, p < .05). However, the majority of them hold positive perception to their body parts, exhibiting a healthy body image perception